2010
DOI: 10.1021/ol101105v
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Syntheses of the Proposed Structures of Cytotoxic Macrolides Iriomoteolide-1a and -1b

Abstract: Enantioselective total syntheses of the proposed structures of macrolide cytotoxic agents iriomoteolide-1a and 1b have been accomplished. The synthesis was carried out in a convergent and stereoselective manner. However, the present work suggests that the reported structures have been assigned incorrectly. The synthesis features Julia-Kocienski olefination, Sharpless asymmetric epoxidation, Brown asymmetric crotylboration, a Sakurai reaction, an aldol reaction, and enzymatic resolution as the key steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…380 Similarly, an enantioselective total synthesis of the proposed structure of iriomoteolide-1b, 381 also isolated from an Amphidinium species, suggested that the proposed structure of this metabolite also needs to be re-examined. 382 Reductive cyclisation of 2-nitrobenzamides to quinazolinobenzodiazepine alkaloids was utilised in synthesis of circumdatin J, 383 a metabolite of Aspergillus ostianus, 384 while a highly convergent synthetic strategy was utilised in the synthesis of circumdatin H. 383,385 DNA of the marine bacterium Pseudoalteromonas tunicata D2 386 was used to create a large insert library in E. coli. Screening of this library resulted in identification of a tambjamine 387 as a nematocide and detection and identification of a large gene cluster encoding for its biosynthesis.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…380 Similarly, an enantioselective total synthesis of the proposed structure of iriomoteolide-1b, 381 also isolated from an Amphidinium species, suggested that the proposed structure of this metabolite also needs to be re-examined. 382 Reductive cyclisation of 2-nitrobenzamides to quinazolinobenzodiazepine alkaloids was utilised in synthesis of circumdatin J, 383 a metabolite of Aspergillus ostianus, 384 while a highly convergent synthetic strategy was utilised in the synthesis of circumdatin H. 383,385 DNA of the marine bacterium Pseudoalteromonas tunicata D2 386 was used to create a large insert library in E. coli. Screening of this library resulted in identification of a tambjamine 387 as a nematocide and detection and identification of a large gene cluster encoding for its biosynthesis.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…zamamistatin), or was substantially extended beyond the first report of structural misassignment. Misassigned natural products (Figure 4) for which revised constitutions have yet to be presented include sponge-derived muzitone, 149 the anti-inflammatory gorgonian metabolites elisabethadione and elisabethamine, 150 iriomoteolides 1a–1c, 151155 and likely marine actinomyceteanthraquinone δ-indomycinone. 156 In all of these cases, total synthesis of the proposed structures revealed discrepancies between the spectroscopic data for the synthetic and natural products.…”
Section: Misassigned Marine Natural Product Structures Not Yet Revmentioning
confidence: 99%
“…One of our main research objectives is to carry out the synthesis of rare and scarce natural products of biological relevance, then investigate their mode of action to obtain insight. Since our first synthesis of hapalosin ( 1 ) in 1996, my laboratory has carried out the synthesis of a range of medicinally important and structurally diverse natural products shown in Figures 1 and 2 6-35…”
Section: Introductionmentioning
confidence: 99%